Associated the Bani Problems and Perspective of Strengthening to Pursue the Formulation of Strategic Management Business Model Holding Company in Indonesia - Abdullah , Edwin Hidayat; Sijabat, Rosdiana; Susilo, Wilhelmus Hary; Herusetya, Antonius (Journal of Ecohumanism, 2024)
The concept of BANI, which stands for Brittle, Anxious, Nonlinear, and Incomprehensible, has emerged as a framework to articulate common problem situations in strategic business. This paradigm provides a worldview for state-owned enterprise business Holding, offering a way to comprehend and navigate the complexities associated with strategy formulation, business synergies, and integration. By orchestrating strategic activities within the business ecosystem, this paradigm aims to achieve sustainable business control and competitive advantage. The inquiries were on understanding of the experiences among experts within strategic formulation, business synergy, and integration. The purpose of the studies was including; determining the business strategy planning of the holding members to achieve competitive advantage in Holding, the actions taken by the holding company to create synergy in the managed business ecosystem of Holding PT Aviasi Pariwisata Indonesia (persero), and the controlling the integration of the business ecosystem implemented to achieve competitive advantage in Holding PT Aviasi Pariwisata Indonesia (persero) for long-term purposes Qualitative research using a descriptive phenomenology design was employed as the methodology. The results pertain of the strategic formulated have fourteen files and one hundred and thirty-one references, the synergy have fourteen files and eighty-one references and also the business integration have thirteen files and fifty-three references. The findings revealed three major themes: strategic formulation, business synergy improvement, and business integration. The study concludes by proposing an orchestration model that strengthens the holding company based on the business ecosystem, incorporating a one-directional development strategy and supported by effective leadership roles.